The Shift of Aqidah and Teenager Morals In The Digital Era - Jasmaludin; Hayati, Hayati (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2024)
The digital era brings significant changes in various aspects of life, including the mindset, behavior, and values embraced by the younger generation. The rapid development of information and communication technology has given teenagers unlimited access to various sources of information, culture, and lifestyles from around the world. This research aims to identify the shift in the beliefs and morals of teenagers in the digital era, especially among school-aged adolescents, and to determine the main factors behind this shift in their beliefs and morals. The research method used is the library method. This method was chosen so that the research can produce a comprehensive understanding based on relevant data sources. The researcher focuses on a discussion that moves from general to specific, starting with an explanation of the concepts of aqidah and akhlak, then discussing the challenges of aqidah in the digital era, the challenges of akhlak in the digital era, efforts to strengthen aqidah and akhlak in the digital era, and concluding with a discussion on the impact of the shift in aqidah and akhlak on adolescents. The efforts made by parents in addressing the shift in faith and morals among teenagers in the digital era are Parents need to create a warm and open relationship with their children, so that teenagers feel comfortable discussing religious and moral values. Instilling religious values from an early age through formal and non-formal education, as well as setting an example in daily life. Supervising the use of technology with a non-restrictive approach, such as using parental controls, discussing appropriate content, and providing guidance on media ethics.